Edukasi dan Bimbingan Terhadap Para Remaja Putri Tentang “Hukum-Hukum Haidl” Di Desa Pranggang Kediri - Alfin Lailatul Mufarichah; Siti Kalimah (LP3M IAIFA Kediri, 2020)
Many of the young women who have experienced menstruation, but do not know the laws of menstruation. Most of them only get a little lesson from their parents because their parents also lack understanding about the laws of menstruation. Based on that context, educational and guidance programs for young women on